ChemInform Abstract: Chelate‐Assisted Direct Selenation of Aryl C—H Bonds with Diselenides Catalyzed by Palladium. Issue 12 (March 2015) - Iwasaki, Masayuki; Tsuchiya, Yuta; Nakajima, Kiyohiko; Nishihara, Yasushi
Abstract The first palladium‐catalyzed C—H selenation of benzamides, benzylamines, and 2‐arylpyridines with the aid of the nitrogen‐chelating groups is developed.